高圧水素環境におけるV添加析出強化型高Mnオーステナイト鋼のき裂進展加速機構 - 三浦, 滉大; 髙桑, 脩; 佐治, 篤; 舘, 幸生; 岩野, 竜也 (鉄と鋼, 2024)
To verify the crack growth resistance of the V-added precipitation-strengthened high-Mn austenitic steel subject to a static and dynamic loading in a hydrogenated environment, the fracture toughness test and two types of fatigue crack growth (FCG) test, i.e., stress intensity factor range ΔK-increasing and ΔK-constant tests were performed under high-pressure gaseous hydrogen environment under the pressure of 95 MPa. The fracture toughness dramatically decreased from 95 to 35 MPa･m1/2 by hydrogen occlusion. The fracture surface consists of intergranular fracture aspects in gaseous hydrogen despite being covered by the dimples tested in air. The FCG acceleration was also pronounced: more acceleration emerged as the ΔK became higher. When changing the loading frequency f as 1, 0.1, 0.01, and 0.001 Hz under constant ΔK of 30MPa･m1/2, the relative FCG rate in gaseous hydrogen to that in air became higher as f decreased, i.e., the dependency of FCG acceleration on the crack opening time. However, the acceleration did not completely depend on the crack opening time, which means a part of FCG acceleration was dominated by crack tip plasticity under cyclic loading. The scanning electron microscopy (SEM) characterization, including the electron-channeling contrast (ECC) imaging and the electron backscatter diffraction (EBSD) analysis, demonstrated that the crack preferentially propagates along grain boundary in the hydrogenated environment. The micro-void and/or micro-crack ahead of the primary FCG crack initiated at the M23C6 carbides precipitated at the grain boundary, which triggered the dramatic acceleration of FCG under 95 MPa gaseous hydrogen.